PERBEDAAN KEEFEKTIFAN ANTARA CLOZAPINE(CLORILEX)DENGAN ELECTRO CONVULSIVE THERAPY(ECT)DALAM PENATALAKSANAAN SKIZOFRENIA RESISTEN OBAT DI RUMAH SAKIT JIWA DAERAH SURAKARTA - H.M. Fanani (Wacana, 2013)
Background: Schizophrenia is chronic and relapse psychotic disorders. It is prevalence is 1-3% based on report from a lot of Country. In general,10 until 60% schizophrenia patient have poor response although using second generation antipsychotic agent. Early identification treatment-resistant schizophrenia very important to give specific treatment from beginning and developed clinical decrease can be reduced. Studies show that clozapine is best agent for treatment-resistant schizophrenia with response about 50% but there is no study that compare to electro convulsive therapy. Objective: To assess the effectiveness of Clozapine (Clorilex) on the intensity of symptom in patients with treatment-resistant schizophrenia. Methods: This randomized experimental research design was used in pretest-post-test control group design. The subjects were all patients with symptoms of treatment-resistant schizophrenia, who underwent therapy in the Surakarta Mental Hospital and meet the study inclusion criteria. Sampling was by consecutive sampling. Research instruments were the PANSS to measure the degree of symptom. The collected data were processed and analyzed using SPSS version 17.0. Chi square test and t test, the significance of variables relations with significance level 5%. Results: There was significant difference between the Clozapine group compared with the electro convulsive therapy group (t= 4,250; p= 0,00). Conclusion: Clozapine (Clorilex) more effective than ECT for resistant schizophreniatreatment. Keywords: Schizophrenia,Clozapine, ECT